Evaluation of Medication Use Patterns among Geriatric Patients using World Health Organization Prescribing Indicators - Irma M. Puspitasari; Ani Hanifah; Rano K. Sinuraya (Universitas Padjadjaran, Indonesia)
Geriatrics patients are paticularly suceptible to medication error due to complex clinical problems and multiple treatment. World Health Organization (WHO) published a set of prescribing indicators to promote rationale use of drug. This study aimed to evaluate medicine use pattern in geriatric patients at a primary care facility in Bandung, Indonesia, using WHO indicators. This research was conducted using cross sectional design with retrospective data collection. Medical presciption from geriatric patients aged 60-74 years old visiting primary care facility during 2013-2015 were selected. A total of 103.292 prescriptions were obtained in this study. The average number of drugs per encounter was 2.1 (optimal range=1.6-1.8). Vast majority (99.41%) of the drugs prescribed were generic drugs (optimal value=100%). The encounters with an antibiotics prescribed were 7.4% (optimal range=20.0-26.8%). Very few parenteral drugs were prescribed in this study setting (0.04%) (optimal range=13.4-24.1%). The drugs prescribed from essential drug list were 72.83% (optimal value=100%). The most commonly prescribed drugs were paracetamol 500 mg, chlorpheniramine maleat 4 mg, amlodipine 5 mg, vitamin B complex, and glyceryl guaiacolat. The most frequently prescribed antibiotics were amoxicillin, cloramphenicol, cyprofloxacin, clindamycin, and oxytetracyclin. In conclusion, the medication use pattern in this study was below the WHO requirement. This finding called for a strategy to promote rational prescribing of medicines. Keywords: geriatrics, WHO prescribing indicators, drug use patterns